Incidence of Rapid and Slow Acetylators of Isoniazid in NWFP - Ghaffar, Abdul; Akhtar, Tasleem; Safi, Muhammad Iqbal; Bokhari, Subhanullah (Journal of Postgraduate Medical Institute, 2011)
In order to determine the phenotype frequencies of rapid and slow acetylators of Isoniazid in NWFP, fifty four tuberculous patient volunteers, who had not bad anti-tubercular treatment before, were studied. The concentration of free and total INH, plasma half life and serum transaminase levels were measured. The rapid acetylators constituted 48.1% in this population. All patients, especially the rapid acetylators receiving INH, should be carefully evaluated for symptoms of hepatitis and serum transaminase levels measured at monthly intervals, so that patients with elevated transaminase levels be taken off the hepatotoxic drugs and alternative drugs administered to them.